Penciptaan Kostum Tari Wayang Wong Ngereka Seraga Japatuan - Adnyana, I Ketut Agus Putra; Mertanadi, I Made; Berata, I Made (Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
The existence of the Wayang Wong Mask in community interlocution events in the current era has experienced a downturn, which in fact is low in appreciation and a decline in the interest of the millennial generation in its continuation. This phenomenon is because wayang wong dances are mostly performed on certain days, and most wayang wong dances are sacred arts. This very interesting issue was raised as a basis for the creation of new creative wayang wong mask costumes, in the form of creating a wayang wong dance costume set which was packaged innovatively entitled